Tandem Hock and Friedel–Crafts reactions allowing an expedient synthesis of a cyclolignan-type scaffold - Ikonnikova, Viktoria A.; Cheibas, Cristina; Gayraud, Oscar; Bosnidou, Alexandra E.; Casaretto, Nicolas; Frison, Gilles; Nay, Bastien (Beilstein Journal of Organic Chemistry, 2024)
The Hock cleavage, which is compatible with tandem processes, was applied to the synthesis of 1-aryltetralines through a one-pot transformation from readily available benzyl(prenyl)malonate substrates. After the photooxygenation of the prenyl moiety, the resulting hydroperoxide was directly engaged in a Hock cleavage by adding a Lewis acid. The presence of an aromatic nucleophile in the reaction mixture and that of a benzyl moiety on the substrate resulted in tandem Friedel–Crafts reactions to form the 1-aryltetraline products. These compounds share a close analogy to the cyclolignan natural products. Experimental observations and a DFT study support the involvement of an aldehyde intermediate during the Friedel–Crafts reactions, rather than an oxocarbenium.
Keywords: 1-aryltetralines; Friedel–Crafts reaction; Hock rearrangement; oxidative cleavage; tandem reactions